Cyst growth, polycystins, and primary cilia in autosomal dominant polycystic kidney disease - Seung Hun Lee; Stefan Somlo (The Korean Society of Nephrology, 2014)
The primary cilium of renal epithelia acts as a transducer of extracellular stimuli. Polycystin (PC)1 is the protein encoded by the PKD1 gene that is responsible for the most common and severe form of autosomal dominant polycystic kidney disease (ADPKD). PC1 forms a complex with PC2 via their respective carboxy-terminal tails. Both proteins are expressed in the primary cilia. Mutations in either gene affect the normal architecture of renal tubules, giving rise to ADPKD. PC1 has been proposed as a receptor that modulates calcium signals via the PC2 channel protein. The effect of PC1 dosage has been described as the rate-limiting modulator of cystic disease. Reduced levels of PC1 or disruption of the balance in PC1/PC2 level can lead to the clinical features of ADPKD, without complete inactivation. Recent data show that ADPKD resulting from inactivation of polycystins can be markedly slowed if structurally intact cilia are also disrupted at the same time. Despite the fact that no single model or mechanism from these has been able to describe exclusively the pathogenesis of cystic kidney disease, these findings suggest the existence of a novel cilia-dependent, cyst-promoting pathway that is normally repressed by polycystin function. The results enable us to rethink our current understanding of genetics and cilia signaling pathways of ADPKD.